FAKTOR MAKRO EKONOMI YANG MEMPENGARUHI PERTUMBUHAN YIELD OBLIGASI - Kurnianingsih, Asih (Jurnal Manajemen Retail, 2021)
This study aims to see the effect of economic factors that contain interest and inflation on the results of the delay proxied by yield to maturity (YTM). The research method uses a causal approach. Samples of data were taken as many as 51 negotiations issued in the 2016-2019 period from companies listed on the Indonesia Stock Exchange. The data analysis technique uses multiple linear regression models and is processed with the SPSS version 23.00 program. The results showed that the interest rate had a positive effect on the result of postponement and inflation had a positive effect on the result of the postponement at a significance level of 5%. It can be found that corporate decisions in Indonesia issued in 2016-2019 can be based on economic factors in the form of interest rates and inflation.